Assessment of Body Mass Index and selected health risk factors among faculty and staff of a Philippine university (Philippine Journal of Nutrition, 2006)
This study examined the association of body mass index (BMI) and selected health risk factors using the 2004 data on the annual medical examination of the University of the Philippines Los Baños (UPLB) faculty and staff. A total of 502 individuals with complete records of weight, height, systolic and diastolic blood pressure, fasting blood sugar (FBS) and total cholesterol were included in the study. Prevalence rates, cross tabulation, means and SDs were used as descriptive statistics. Analysis of variance was used to compare BMI and selected health risk factors (hypertension, hypercholesterolemia and hyperglycemia) across sex- and age- specific groups. Correlation analysis was used to investigate the association of BMI with the selected health risk factors. Results showed that 76.1% were above the BMI cut off for normal body weight, that is, 46.8% were overweight and 29.3% were obese. Prevalence of hypercholesterolemia was 22.3%, hypertension was 13.9% for high diastolic blood pressure and 9.8% for high systolic blood pressure, and hyperglycemia was 4.5%. High diastolic and systolic blood pressures were highly prevalent among men than women while hypercholesterolemia was prevalent both in men and women. Total cholesterol, ana systolic and diastolic blood pressures were significantly correlated with BMI. These findings are vital inputs in the development of interventions that focus on health promotion and prevention of these risk factors.